Pharmacognostical Evaluation on the Root of Rotula Aquatica Lour. - MAMTA K; ABHISHEK B; ROHIT (International Journal of Pharma and Bio Sciences, 2010)
The root of Rotula aquatica is also called as pashanbed, belonging to the family Borogenaceae. It is widely distributed in India from kumaun to Assam and western to southern India.The medicinal values of plant lie in their component phytochemicals such as alkaloids, flavonoids, phenolic compounds and other nutrients like as amino acid, proteins, which produce a definite physiological action on the human body. The present study attempts pharmacognostic studies of root, extraction, identification of chemical constituents from the crude extracts of different extracts of Rotula aquatica.Macroscopic as well as microscopic studies of any crude drug are the primary steps to establish its botanical quality control before going to other studies. Hence phamacognostic studies of crude drug play a very important role in identifying the purity and quality of crude drugs. The present investigation reveals phamacognostic characters which include morphology, T.S, Powder microscopy, Phytochemical screening, and further isolation and identification of Phytoconstituents from ethanolic extract of Rotula aquatica.